Pandangan remaja pedesaan terhadap program keluarga berencana - Adam, Subagyo (Lembaga Penelitian, Universitas Airlangga, 1990)
Understanding the family planning program among the rural adolescent in Kecamatan Kertosono, Kabupaten Nganjuk, Jawa Timur Province.